Hypocalcemia is associated with adverse outcomes in patients with diabetes and COVID-19 - Xu, Xinyue; Zhu, Qin; Yang, Yaling; Liu, Jia; Wu, Chenwei; Qu, Duoduo; Wang, Chunhong; Zhao, Xiaolong (Frontiers in Endocrinology, 2025)
BackgroundPatients with diabetes and COVID-19 have a worse prognosis. The aim of this study was to investigate the prevalence of hypocalcemia in patients with diabetes and COVID-19, and assess the relationship between serum calcium levels and prognosis in these patients.MethodsA retrospective analysis was conducted on 919 patients with diabetes admitted for COVID-19 from February 2022 to May 2022. The population was categorized into three groups according to serum calcium levels. The primary outcome was the risk of developing severe COVID-19, and the secondary outcomes included the risk of requiring advanced respiratory support (including high-flow oxygen, non-invasive ventilation, and invasive ventilation). Logistic regression analysis was used to evaluate the association between hypocalcemia and the prognosis of COVID-19 patients with diabetes.ResultAmong the 919 patients with diabetes, the median age was 70 (56-81) years, and 498 (54.2%) were male. The prevalence of hypocalcemia in COVID-19 patients with diabetes was 78.8%. The serum calcium level was negatively correlated with inflammatory markers (hsCRP, ESR, PCT, IFN). The serum calcium level was positively correlated with albumin, CD4+ T cell counts, and CD8+ T cell counts. In Multivariate analysis, after adjustment for age and gender, the higher risk of severe illness was observed in patients with a serum calcium level <1.94 mmol/L (OR 2.86, 95%CI [1.78-4.59], P<0.001).ConclusionAdmission serum calcium level is associated with the prognosis of COVID-19 patients with diabetes. Hypocalcemia increases the risk of progression to severe COVID-19 in patients with diabetes.